Ethics of Population Administration Services (Case Study at the Department of Population and Civil Registration of Pekanbaru City) - Suci Angraini Suci; Indah Adi Putri; Roni Ekha Putera (Journal of Public Administration and Government, 2022)
Ethics must always be considered in every phase of public service. If every apparatus has ethics in public services, the organization will be able to achieve the ultimate goal of service, namely providing services with good performance in order to provide satisfaction to the public. This study uses a qualitative method with descriptive analysis type of research. Judging from the indicators of public service ethics consisting of equality, equity, loyalty, and responsibility. In conclusion, population administration and civil registration services in providing services to the community are not maximal enough, because population administration services are still slow and convoluted.